Environmental Governance through the Utilization of Waste Methane Gas into Renewable Energy - Thuerry Prak Sevann (Journal La Lifesci, 2021)
The purpose of this article is to examine the conversion of waste methane gas to renewable energy through environmental management. Processing organic waste is one kind of alternative energy that may be generated and regenerated. Garbage is a major issue for the majority of people, particularly the vast volume of market garbage. Waste processing and utilization technology is required. Implementing the 3R process of reduce, reuse, and recycle on fresh garbage not only generates useful goods, but also addresses the waste issue and generates revenue for those who wish to manage it. As a result, it is critical to evaluate the design of organic waste burners that convert methane gas to methane and to estimate the rate of combustion and heat produced by organic waste biogas